2019
DOI: 10.1101/792473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant connectivity in auditory precision encoding in schizophrenia spectrum disorder and across the continuum of psychotic-like experiences

Abstract: BackgroundThe ability to generate a precise internal model of statistical regularities is impaired in schizophrenia. Predictive coding accounts of schizophrenia suggest that psychotic symptoms may be explained by a failure to build precise beliefs or a model of the world. The precision of this model may vary with context. For example, in a noisy environment the model will be more imprecise compared to a model built in an environment with lower noise. However compelling, this idea has not yet been empirically s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Instead, previous studies have shown that neuronal responses scale with the spectral distribution of auditory stimulation, a finding showing a dynamic variation in stimulus-specific adaptation, interpreted as adaptation to stimulus statistics ( Herrmann et al, 2013 , 2014 ). Indeed, several findings indicate that alphabet size ( Winkler et al, 1992 ; Barascud et al, 2016 ; Auksztulewicz et al, 2017 ; Quiroga-Martinez et al, 2019 , 2020 ) or the width of the distribution ( Garrido et al, 2013 ; Larsen et al, 2020 ) of the stimulation sequence are reflected on neural signals, supporting the idea that variability in the stimulation (inverse precision) plays a role in the modulation of deviance detection. In our study, decreasing the confidence (from oddball to random) increases the spectral variability of the stimulation (i.e., tones of different frequencies become more probable), without broadening the spectral range of the sequence.…”
Section: Discussionmentioning
confidence: 91%
“…Instead, previous studies have shown that neuronal responses scale with the spectral distribution of auditory stimulation, a finding showing a dynamic variation in stimulus-specific adaptation, interpreted as adaptation to stimulus statistics ( Herrmann et al, 2013 , 2014 ). Indeed, several findings indicate that alphabet size ( Winkler et al, 1992 ; Barascud et al, 2016 ; Auksztulewicz et al, 2017 ; Quiroga-Martinez et al, 2019 , 2020 ) or the width of the distribution ( Garrido et al, 2013 ; Larsen et al, 2020 ) of the stimulation sequence are reflected on neural signals, supporting the idea that variability in the stimulation (inverse precision) plays a role in the modulation of deviance detection. In our study, decreasing the confidence (from oddball to random) increases the spectral variability of the stimulation (i.e., tones of different frequencies become more probable), without broadening the spectral range of the sequence.…”
Section: Discussionmentioning
confidence: 91%
“…They used the community assessment of psychic experience (CAPE) in all participants to assess psychotic-like experiences across the continuum and their association with connectivity parameters related to precision encoding. They found a negative correlation between CAPE+ and lateral connections in right and left IFG and top-down connections from right IFG to STG, which is important in encoding precision (Larsen et al, 2020). This suggests that aberrant predictive activity and precision encoding in these connections is associated with increased CAPE+ scores.…”
Section: Integrating Rdoc and Pp: A Framework For Understanding Psych...mentioning
confidence: 97%
“…This process could begin with identifying an interpretable physiological component that could explained in terms of the PP framework (e.g., MMN as a prediction error) that demonstrates variability across a spectrum of psychiatric conditions (Randeniya et al, 2018) (Fig 2A). This spectrum includes individuals at high risk of a condition as well as those with established psychiatric disorders (Larsen et al, 2020;Randeniya et al, 2018).…”
Section: Integrating Rdoc and Pp: A Framework For Understanding Psych...mentioning
confidence: 99%
See 2 more Smart Citations